Comparative analysis of selected market solutions for e-learning systems - Szalach, Adam Jakub (Folia Toruniensia, 2018)
Aim: The aim of the article is to present e-learning as a tool that in the era of ubiquitous computerization is one of the largest teaching support systems, both for students and for teachers. Research method: The author carried out a comparative analysis, wanting to show the differences between the discussed e-learning platforms, at the same time indicating the strengths and weaknesses of this tool, used as didactic support for traditional forms of teaching. Conclusions: The organization of work with the e-learning system depends to a large extent on its architecture, configuration or didactic tasks that such a system should meet. Particular attention should be paid to the fact that the differences may arise from systems based on the so-called free and commercial licenses, where both have their advantages and disadvantages.